POTENTIAL OF CARBON STORAGE OF RUBBER (Hevea brasiliensis MÃœLL. ARG.) PLANTATIONS IN MONOCULTURE AND AGROFORESTRY SYSTEMS IN THE COLOMBIAN AMAZON - HernÃ¡n Jair Andrade; J. Orjuela-Chavez; Y. Vargas-Valenzuela (Tropical and Subtropical Agroecosystems, 2014)
Carbon sequestration potential of rubber (Hevea brasiliensis) plantations was estimated in two production systems: monoculture and agroforestry system with copoazÃº (Theobroma grandiflorum), on farms of Florencia, El Doncello and BelÃ©n de los AndaquÃes, in northeastern Colombian Amazon, department of CaquetÃ¡. The plantations were classified into three age classes, according to their productive stage: 1-7, 8-20 and > 20 years. The carbon storage was estimated using the methodology proposed by Andrade and Ibrahim (2003) and recommended by IPCC (2003). Tree carbon sinks were evaluated: above and below ground biomass, and necromass. The highest proportion of carbon storage was found in biomass, with 95 and 92% in monoculture plantations and agroforestry systems, respectively. In both types of production systems, carbon storage is a function of tree age and density. The carbon stored in monoculture plantations was higher than in agroforestry systems, due to a greater density of rubber trees in the first production system. This study confirms that rubber plantations have potential to capture and store atmospheric carbon. With this information, the issue of participating in carbon markets of the rubber production chain can be addressed, and therefore strengthen in the regionâ€™s competitiveness and sustainability.